A Strategic Evaluation of Clean Coal Technology as an Accelerator for Net Zero Emission Targets in the Electricity Sector - William, Milanda; Noko, Keith (Journal of Current Research In Multidisciplinary, 2025)
The global urgency to mitigate climate change has pushed the power generation sector toward a rapid energy transition. This study, titled "A Strategic Evaluation of Clean Coal Technology as an Accelerator for Net Zero Emission Targets in the Electricity Sector," examines the pivotal role of Clean Coal Technology (CCT) in bridging the gap between current fossil fuel dependency and a future dominated by renewable energy. As many developing nations remain reliant on coal for energy security and affordability, the immediate abandonment of coal assets poses significant economic risks. This research explores how technologies such as High-Efficiency Low-Emission (HELE) systems, Carbon Capture, Utilization, and Storage (CCUS), and biomass co-firing can be strategically deployed to reduce carbon footprints without compromising grid stability. The study employs a qualitative strategic analysis, evaluating the technical feasibility, economic viability, and environmental impact of these innovations. The findings suggest that CCT should not be viewed as a long-term alternative to renewables, but rather as a critical strategic accelerator that allows for a "just transition." By modernizing existing infrastructure, countries can achieve significant emission reductions in the short to medium term while building the financial and technical capacity required for a full renewable shift. Ultimately, this research provides a framework for policymakers and utility managers to integrate CCT into their broader Net Zero Emission (NZE) roadmaps.